Fullerenes in Circumstellar and Interstellar Environments. (5th March 2015) - Cami, Jan
Abstract: In recent years, the fullerene species C60 (and to a lesser extent also C70 ) has been reported in the mid-IR spectra of various astronomical objects. Cosmic fullerenes form in the circumstellar material of evolved stars, and survive in the interstellar medium (ISM). It is not entirely clear how they form or what their excitation mechanism is.